Establishment of a Mycoplasma hyorhinis challenge model in 5-week-old piglets - Földi, Dorottya; Nagy, Zsófia Eszter; Belecz, Nikolett; Szeredi, Levente; Földi, József; Kollár, Anna; Tenk, Miklós; Kreizinger, Zsuzsa; Gyuranecz, Miklós (Frontiers in Microbiology, 2023)
Introduction Mycoplasma hyorhinis is an emerging swine pathogen with high prevalence worldwide. The main lesions caused are arthritis and polyserositis, and the clinical manifestation of the disease may result in significant economic losses due to decreased weight gain and enhanced medical costs. We aimed to compare two challenge routes to induce M. hyorhinis infection using the same clinical isolate. Methods Five-week-old, Choice hybrid pigs were inoculated on 2 consecutive days by intravenous route (Group IV-IV) or by intravenous and intraperitoneal routes (Group IV-IP). Mock-infected animals were used as control (control group). After the challenge, the clinical signs were recorded for 28 days, after which the animals were euthanized. Gross pathological and histopathological examinations, PCR detection, isolation, and genotyping of the re-isolated Mycoplasma sp. and culture of bacteria other than Mycoplasma sp. were carried out. The ELISA test was used to detect anti-M. hyorhinis immunoglobulins in the sera of all animals. Results Pericarditis and polyarthritis were observed in both challenge groups; however, the serositis was more severe in Group IV-IV. Statistically significant differences were detected between the challenged groups and the control group regarding the average daily weight gain, pathological scores, and ELISA titers. Additionally, histopathological scores in Group IV-IV differed significantly from the scores in the control group. All re-isolated strains were the same or a close genetic variant of the original challenge strain. Discussion Our results indicate that both challenge routes are suitable for modeling the disease. However, due to the evoked more severe pathological lesions and the application being similar to the hypothesized natural route of infection in Group IV-IV, the two-dose intravenous challenge is recommended by the authors to induce serositis and arthritis associated with M. hyorhinis infection.